Investigating and calculating the temperature of hot-spot factor for transformers - Khalid Yahya; Hani Attar; Haitham Issa; Jamal Ali Ramadan Dofan; Nassim A. Iqteit; Adel E. M. Yahya; Ahmed Amin Ahmed Solyman (Institute of Advanced Engineering and Science, 2023)
This article explores the measurement of temperature in transient states, utilizing the principles of heat transfer and thermal-electrical metaphor. The study focuses on the nonlinear thermal resistances present in various locations within a distribution transformer, while taking into account variations in oil physical variables and temperature loss. Real-time data obtained from heat run tests on a 250-MVA-ONAF cooled unit, conducted by the transformer manufacturer, is used to verify the thermal designs. The observations are then compared to the loading framework of the IEC 60076-7:2005 system. The findings of this research provide a better understanding of temperature measurement in transient states, particularly in distribution transformers, and can be applied to the design and development of more efficient and reliable transformer systems.